2019
DOI: 10.1002/gcc.22787
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide DNA methylation analysis of colorectal adenomas with and without recurrence reveals an association between cytosine‐phosphate‐guanine methylation and histological subtypes

Abstract: Aberrant methylation of DNA is supposed to be a major and early driver of colonic adenoma development, which may result in colorectal cancer (CRC). Although gene methylation assays are used already for CRC screening, differential epigenetic alterations of recurring and nonrecurring colorectal adenomas have yet not been systematically investigated. Here, we collected a sample set of formalin‐fixed paraffin‐embedded colorectal low‐grade adenomas (n = 72) consisting of primary adenomas without and with recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Conversely, hypomethylation often occurs in the open sea area of the genome. A similar pattern has been observed in another study where hypomethylation of CpG sites was enriched at the open sea area and intergenic region [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, hypomethylation often occurs in the open sea area of the genome. A similar pattern has been observed in another study where hypomethylation of CpG sites was enriched at the open sea area and intergenic region [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 87%
“…In this regard, present surveillance programs, based on size, morphology, and absence of synchronous polyps, frequently result in unnecessary repeated colonoscopy. This implies the need of identifying novel noninvasive, selective, and reliable markers for improving the stratification and the follow-up of those specific patients at higher CRC risk [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiologic studies have shown the efficacy of endoscopic screening [ 23 ], colonoscopy monitoring has some strong limitations that can considerably affect its effectiveness: (i) the intervals are defined according to CRC-risk guidelines considering as main criteria the number and size of the removed polyps but lacking information on important molecular features, (ii) colonoscopy is an invasive procedure [ 25 ], (iii) patients show a low adherence to the surveillance program, and (iv) this type of screening is associated with high costs for the National Health Systems (NHS). Therefore, alternative or supportive biomarkers able to reduce unnecessary invasive procedure and predict recurrence are highly required [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TCGA CRC gene expression profile was also downloaded from the UCSC Xena Browser. By a systematic search in the GEO database, 8 methylation datasets of the Illumina 450k array were obtained as test set (N = 930): http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE42752, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE48684, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE68060, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE77718, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE77954, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE101764, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE107352, and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE129364 23‐29 . An additional methylation dataset for the Illumina EPIC array with 4 cell‐free DNA (cfDNA) samples from CRC and 4 samples from healthy controls were obtained from http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE122126 30 …”
Section: Methodsmentioning
confidence: 99%
“…By a systematic search in the GEO database, 8 methylation datasets of the Illumina 450k array were obtained as test set (N = 930): GSE42752, GSE48684, GSE68060, GSE77718, GSE77954, GSE10 1764, GSE10 7352, and GSE12 9364. [23][24][25][26][27][28][29] An additional methylation dataset for the Illumina EPIC array with 4 cell-free DNA (cfDNA) samples from CRC and 4 samples from healthy controls were obtained from GSE12 2126. 30…”
Section: Public Data Collectionmentioning
confidence: 99%